3D imaging shows nano- and microparticles are internalized by salmon skin and corneal epithelial cells - Thiyagarajan, Dhivya B.; Stette, Marie H. S.; Afzal, Bilal M.; Ahluwalia, Balpreet S.; Agarwal, Krishna; Dalmo, Roy A.; Wolfson, Deanna L. (Frontiers in Marine Science, 2024)
The rising problem of plastic pollution is becoming one of the major environmental issues for the world. In the ocean, plastics undergo degradation into smaller microplastics (MPs) and nanoplastics (NPs), which are known to cause problems for every type of marine life, from plankton to seabirds. Norway is one of the biggest producers of Atlantic salmon, which are usually reared in plastic tanks inside open sea cage systems during their life cycle. These cages and other equipment produce even more plastic pollution directly in the salmon habitat, increasing the likely exposure of farmed salmon to NPs and MPs both through skin and through skin wounds. Keratocytes cells are scavenger epithelial cells which help remove foreign materials and maintain the salmon's health; they are therefore first in line to handle and to suffer from MP and NP exposure. While the impacts of MPs have been well studied in many different organisms, much less is known about the effects of NP exposure, particularly at the subcellular level. Here, we have used holotomographic and fluorescence microscopy to show that both skin and corneal salmon keratocyte cells fully internalize 500 -1000 nm polystyrene particles, as well as inorganic 500 nm silica particles. Furthermore, some of these particles likely end up in lysosomal compartments within 2 hours of exposure. As climate change and pollution increase the stresses on marine species, understanding salmon's mechanisms for handling MPs and NPs from both pollution and natural sources may lead to future mitigation strategies; here, we show that both conventional and new modalities of microscopy have a role to play in tackling these challenges.